2007
DOI: 10.1103/physrevlett.98.170402
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Superfluid Interface Scattering for Polarized Fermion Gases

Abstract: We argue that, for the recent experiments with imbalanced fermion gases, a temperature difference may occur between the normal (N) and the gapped superfluid (SF) phase. Using the mean-field formalism, we study particle scattering off the N-SF interface from the deep BCS to the unitary regime. We show that the thermal conductivity across the interface drops exponentially fast with increasing h/k B T , where h is the chemical potential imbalance. This implies a blocking of thermal equilibration between the N and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 21 publications
3
46
0
Order By: Relevance
“…These experiments confirm the theoretical proposal of Parish and Huse [151], who showed that this metastable state could arise due to the elongated trap geometry, in which evaporation occurs predominantly from the trap center. Once phase separation occurs in this geometry, particle and heat transport are suppressed at the narrow interface between the gapped superfluid core and the normal outer region [152,153,151]. It turns out that the resulting evaporative depolarization of the central core stabilizes superfluidity, and thus favors the superfluid phase over the normal phase, even when the overall polarization of the gas is above the expected critical imbalance.…”
Section: Experimental Overviewmentioning
confidence: 97%
“…These experiments confirm the theoretical proposal of Parish and Huse [151], who showed that this metastable state could arise due to the elongated trap geometry, in which evaporation occurs predominantly from the trap center. Once phase separation occurs in this geometry, particle and heat transport are suppressed at the narrow interface between the gapped superfluid core and the normal outer region [152,153,151]. It turns out that the resulting evaporative depolarization of the central core stabilizes superfluidity, and thus favors the superfluid phase over the normal phase, even when the overall polarization of the gas is above the expected critical imbalance.…”
Section: Experimental Overviewmentioning
confidence: 97%
“…Consider an incoming a-particle from the N side with energy E > ξ (p) − µ a , where or k from real to imaginary values (or vice versa), signifying a change in the scattering mechanism as described below [30,31]: i) For E < ∆ − h, the incoming particle has insufficient energy to excite the SF side. In this case we have total reflection.…”
Section: Transmission Coefficientsmentioning
confidence: 99%
“…β ), where κ (0) is the heat conductivity in the absence of the external field and κ (1) is the additional term due to the [30]), which we neglect. Also, in our calculations we have neglected the energy carried by the β-channel because it is quite lower than that carried by the α-channel.…”
Section: Heat Conductivitymentioning
confidence: 99%
See 2 more Smart Citations